Ophthalmic Complications of Dengue Fever - Humaira Zakir, Abdul Rabb Bhutto, Muneer Sadiq, Waqas Manzoor, Asif Mashood Qazi, Vijay Kumar, Hina Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Dengue fever, a mosquito-borne viral illness, has become a major public health issue, especially in endemic regions. Although primarily known for its systemic symptoms, emerging evidence suggests that dengue can also result in ophthalmic complications. Objective: To determine the incidence, types, and clinical significance of ophthalmic manifestations among patients with dengue fever. Methods: This retrospective observational study was conducted at Al-Tibri Medical College and Hospital between 2015 and 2020. Medical records of 600 serologically confirmed dengue patients were reviewed. Patients who developed ocular symptoms during or within two weeks of illness onset were included. Data on demographics, clinical and laboratory findings, and detailed ophthalmic evaluations were analyzed using SPSS software. Results: Of the 600 patients, 50 (6.25%) developed ophthalmic complications. The mean age was 34 years, with a male predominance (60%). The most common complication was conjunctivitis (60%), followed by uveitis (12%), optic neuritis (8%), retinal hemorrhages (6%), and macular edema (4%). Unilateral involvement was observed in 61.83% of cases, while 38.16% had bilateral eye symptoms. All complications were self-limiting, resolving within two weeks without hospitalization. Conclusion: Ophthalmic involvement in dengue fever, although relatively uncommon, can be clinically significant. Early recognition and ophthalmologic evaluation in dengue patients presenting with visual complaints are crucial to avoid potential long-term visual impairment. Increased clinical vigilance and further studies are recommended to better understand and manage these complications. Keywords: Dengue fever, ophthalmic complications, uveitis, conjunctivitis, retinal hemorrhage, optic neuritis, macular edema, viral infection, visual impairment.